The Impact of Statin Use and Breast Cancer Recurrence - A Retrospective Study in Singapore - Sim, Yirong; Lim, Cindy; Phyu, Nitar; Tan, Kiat Tee Benita; Chew, Lita Sui Tjien; Wong, Chow Yin; Madhukumar, Preetha; Yong, Wei Sean; Lim, Sue Zann; Hamzah, Julie Liana Bte; Tan, Si Ying; Chay, Wen Yee; et al. (Frontiers in Oncology, 2022)
Introduction Statins, HMG-CoA reductase inhibitors, are commonly used cholesterol-lowering medications which are also increasingly recognized to have anti-cancer properties for various cancers, including breast cancer. Most clinical evidence supports a protective effect of statin on reducing breast cancer recurrence, particularly in hormone-receptor positive breast cancers.This study seeks to study the impact of statin use on breast cancer recurrence in an Asian population. Methods This is a retrospective study of patients diagnosed with breast cancer at the National Cancer Centre and Singapore General Hospital from 2005-2015. Statin use was defined as use after surgery. Associations between statin use, breast cancer recurrence and overall survival were estimated using Cox proportional hazards regression with adjustment for age, TNM stage, grade, ER/HER2 status, and co-morbidities. Associations between statin-use and disease-specific survival were estimated using competing risks regression. Results A total of 7858 females with breast cancer were studied, 1353(17.2%) were statin users, 6505(82.8%) were non-statin users, with a median follow-up of 8.67 years. Distribution of cancer stage, histology, molecular subtypes and grades were similar in both groups. Estrogen receptor(ER) positive (HR 0.57,95%CI 0.43-0.76,p<0.001) and HER2 negative (HR 0.74,95%CI 0.57-0.96,p=0.026) invasive cancers had a lower risk of recurrence in statin users. Statin users trended towards a long term recurrence-risk reduction (all subtypes,HR 0.48,p=0.002; ER-, HR 0.34,p=0.036; HER2+,HR 0.10,p=0.002). The risk-reduction benefit is not appreciated in statin users with DCIS, possibly due to small recurrence event numbers. Disease-specific survival benefit was seen in statin users with ER+ cancers (adjusted SHR 0.71,95%CI 0.53-0.96,p=0.027), especially ER+ invasive cancers (adjusted SHR 0.72, 95%CI 0.53-0.97,p=0.028), but with no statistically significant benefit in overall survival for statin users (all subtypes). Conclusion This is the first known retrospective study on the effect of statin use and breast cancer recurrence in an Asian population. Similar to previous international studies, statin use is associated with a risk reduction in breast cancer recurrence. This is especially beneficial in patients who have ER+ and HER2- invasive breast cancer. Statin use is also associated with a reduced risk of breast cancer recurrence in all subtypes of breast cancer in the long term (>6 years post diagnosis).